Electrophysiological effects of adipose graft transposition procedure (AGTP) on the post-myocardial infarction scar: A multimodal characterization of arrhythmogenic substrate - Adeliño, Raquel; Martínez-Falguera, Daina; Curiel, Carolina; Teis, Albert; Marsal, Roger; Rodríguez-Leor, Oriol; Prat-Vidal, Cristina; Fadeuilhe, Edgar; Aranyó, Júlia; Revuelta-López, Elena; Sarrias, Axel; Bazan, Víctor; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective To assess the arrhythmic safety profile of the adipose graft transposition procedure (AGTP) and its electrophysiological effects on post-myocardial infarction (MI) scar. Background Myocardial repair is a promising treatment for patients with MI. The AGTP is a cardiac reparative therapy that reduces infarct size and improves cardiac function. The impact of AGTP on arrhythmogenesis has not been addressed. Methods MI was induced in 20 swine. Contrast-enhanced magnetic resonance (ce-MRI), electrophysiological study (EPS), and left-ventricular endocardial high-density mapping were performed 15 days post-MI. Animals were randomized 1:1 to AGTP or sham-surgery group and monitored with ECG-Holter. Repeat EPS, endocardial mapping, and ce-MRI were performed 30 days post-intervention. Myocardial SERCA2, Connexin-43 (Cx43), Ryanodine receptor-2 (RyR2), and cardiac troponin-I (cTnI) gene and protein expression were evaluated. Results The AGTP group showed a significant reduction of the total infarct scar, border zone and dense scar mass by ce-MRI (p = 0.04), and a decreased total scar and border zone area in bipolar voltage mapping (p < 0.001). AGTP treatment significantly reduced the area of very-slow conduction velocity (<0.2 m/s) (p = 0.002), the number of deceleration zones (p = 0.029), and the area of fractionated electrograms (p = 0.005). No differences were detected in number of induced or spontaneous ventricular arrhythmias at EPS and Holter-monitoring. SERCA2, Cx43, and RyR2 gene expression were decreased in the infarct core of AGTP-treated animals (p = 0.021, p = 0.018, p = 0.051, respectively). Conclusion AGTP is a safe reparative therapy in terms of arrhythmic risk and provides additional protective effect against adverse electrophysiological remodeling in ischemic heart disease.